Perception of patient-centered care in three fertility clinics: influence of domestic or cross-border treatment and reimbursement policy: Dojemanje oskrbe, osredotočene na pacienta, v treh klinikah za zdravljenje neplodnosti: vpliv zdravljenja v domačem okolju ali tujini in povračila stroškov - Vlaisavljević, Veljko; Kovačič, Borut (Acta Medico-Biotechnica, 2024)
Introduction: This study aimed to evaluate the experience of patients undergoing patient-centered care (PCC) at three fertility clinics in Southeastern Europe in terms of the treatment cost coverage and quality of care provided. Methods: Couples who underwent assisted reproductive technology (ART) were divided into three groups: (i) Slovenian patients covered under the national insurance programme; (ii) self-pay patients receiving treatment in their country of origin/a clinic abroad; and (iii) cross-border self-pay patients receiving treatment in Maribor, Slovenia.A standardized questionnaire, the “Patient Centeredness Questionnaire  on Infertility Treatment (PCQ-Infertility)”, was translated into each patient’s native language and administered to 400 couples, of whom 78% completed it. For each of the three patient groups, the mean scores of the PCC domains and indicators were calculated. These data were then used for the score gap analysis.Results: Overall, the domain assessing the competence level of medical staff produced the biggest score domain gap (SDG) in the group of cross-border, self-pay patients, while the smallest score was observed for the health organization domain in the group of domestic patients with reimbursed cycles. In our research, the indicator corresponding to information about any possible side-effects of the prescribed medication produced the smallest score indicator gap (SIG), while the biggest SIG was observed for staff members assigned to be contacted for questions at any time.Conclusion: The results did not show that the financing method of ART treatment affected patient experiences of PCC. Although the competence of the medical staff is rated highly, domestic patients with reimbursed ART cycles continue to experience a lack of PCC in the health organization domain.
Keywords: assisted reproductive therapy, cross-border patients, patient treatment experience, patient centeredness, quality of care